Studi Alterasi dan Mineralisasi Endapan Hidrotermal di Daerah Jampea, Selayar, Sulawesi Selatan - Andi Febby Alvionita; Muhammad Rivaldi Amri; Irzal Nur; Sri Widodo (Universitas Halu Oleo, 2025)
The sulfide mineralization at each location has distinct mineralization and alteration characteristics depending on its genesis and aspects not previously studied by researchers. This includes the research location, Jampea Island, which requires further identification of several aspects related to sulfide mineralization, such as hydrothermal alteration characteristics, ore and gangue mineral assemblages, mineralization types, and the range of formation temperatures and pH of the hydrothermal fluids that formed them. This study aims to analyze the ore mineral assemblages along with their formation sequence, determine the types of alteration in the research area, and establish a genetic model of sulfide mineralization in the research area. The research was conducted in several stages, including field data collection (samples, location plotting, and documentation), sample preparation, followed by data processing through laboratory analyses consisting of petrographic analysis, mineragraphic analysis, and XRD (X-Ray Diffraction). The results indicate that granite and diorite act as the host rocks for mineralization in the research area. The alteration mineral assemblages associated with mineralization in the research area include quartz, sericite, calcite, chlorite, alkali feldspar, epidote, and dolomite. There are three alteration zones: propylitic, phyllic, and potassic. Mineralization in the research area formed within a temperature range of 200–320°C, with hydrothermal fluid pH ranging from acidic to neutral. The resulting ore mineral assemblages consist of two types: hypogene and supergene, with the minerals including: pyrite, chalcopyrite, bornite, magnetite, chalcocite, and covellite.